IMPLIKASI PENGELOLAAN KRISIS EKONOMI OLEH KONSORSIUM TROIKA TERHADAP EKONOMI DAN POLITIK YUNANI - Febriyana "; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The title of this research is “Implication of economic crisis management by Consortium Troika to economics and politics domestic of Greece during 2009-2012 periode. The management of Greece crisis by Consortium Troika (European Commission, European Central Bank, and International Monetary Fund) as a regime. This research uses international regimes theory and liberalism perspective. The Consortium Troika make the rules, such as bail out, appliying high taxes, etc. As implication of Consortium Troika’s rules, economics Greece is low, wich is characterized by rising unemployment, deficit reduction and a decrease in the tourism sector. The politics domestic condition is not good, make George Papandreou resign to be Greece Prime Minister, Greece public protest, and there is competition of political parties between Demokrasi Baru, Pasok, and Syriza. Key Words: Economic crisis, Consortium Troika, regime, economics and politics domestic of Greece.